2018
DOI: 10.4103/1319-2442.229268
|View full text |Cite
|
Sign up to set email alerts
|

Scoring systems and outcome of chronic kidney disease patients admitted in intensive care units

Abstract: The outcome of chronic kidney disease (CKD) patients admitted to the Intensive Care Unit (ICU) is difficult to predict. This study assessed the outcome of CKD patients admitted to the ICU and evaluated prediction of 30-day mortality using the Acute Physiology and Chronic Health Evaluation (APACHE II), Simplified Acute Physiology Score (SAPS II), and Sequential Organ Failure Assessment (SOFA) score. One hundred consecutive CKD patients admitted to the ICU at a tertiary care hospital, Ahmedabad between 2011 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Glycerol keeps the skin hydrated and supple whereas Paraffin protect the skin from chemical irritant by improving its barrier function [17,18]. Studies on various aspects of chronic renal diseases were reported [19][20][21][22][23]. Studies from Global Injury were reviewed [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…Glycerol keeps the skin hydrated and supple whereas Paraffin protect the skin from chemical irritant by improving its barrier function [17,18]. Studies on various aspects of chronic renal diseases were reported [19][20][21][22][23]. Studies from Global Injury were reviewed [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…There is significant clinician workload associated with calculating CCI and SOFA scores to apply the algorithm to large dialysis programs and hospitals. We acknowledge that SOFA has limits for prognostication, but note its adoption in most ventilator triaging protocols in the United States (39) and reasonable discrimination among patients with AKI (40)(41)(42)(43)(44)(45). Our vetting process identified the importance of objective measures of prognosis; thus, we opted to use the CCI as an amendment to the strategy by White et al (16).…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…However, although the SOFA score has been validated across various populations in ICUs, there is no definitive consensus on its performance in predicting mortality in ICUs [19][20][21][22]. Actually, several previous studies have attempted to validate the discriminatory performance of this scoring system for in-hospital mortality prediction of patients with ESKD in ICUs [23][24][25]. However, inconsistent results were obtained by these studies, possibly due to the heterogeneity of the study populations and settings.…”
Section: Introductionmentioning
confidence: 99%